Answer :

i.

Multiplying numerator and denominator of by 5-3√7; We get,

= {using (a-b)(a + b) = a^{2}-b^{2}}

=

=

Rationalised form of is

ii.

Multiplying numerator and denominator of by ; We get,

Applying : (a-b)(a + b) = a^{2}-b^{2}

=

=

=

Rationalised form of is

iii.

Multiplying numerator and denominator of by ; We get,

using (a-b)(a + b) = a^{2}-b^{2}

=

=

=

Rationalised form of is

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Related Videos

Quiz | Rationalizing the Denominator39 mins

The Curious Case of Irrational Numbers43 mins

Irrational numbers on Number line32 mins

Terminating & Non - Terminating Decimal Expansion51 mins

Quiz on Irrational Numbers31 mins

Quiz | Learning the Laws of Exponents52 mins

Quiz | Irrational Numbers and its Operations45 mins

Champ Quiz | Rationalization30 mins

RD Sharma | Practice Imp.Qs. on Number System48 mins

RD Sharma | Master The Number System40 mins

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation